Three-dimensional porous composite material and its preparation method and electromagnetic microwave absorption application

By using bivalent transition metal ions to induced MXene nanosheet assembly and in situ vulcanization treatment in three-dimensional porous composite MXene/TMS, a non-uniform heterogeneous interface and defect-induced dipole polarization sites are formed, which solves the problems of low absorption performance and narrow absorption bandwidth of existing electromagnetic microwave absorbing materials, and achieves efficient electromagnetic wave loss and infrared stealth performance.

CN115716648BActive Publication Date: 2025-03-04ANHUI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211403230.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-10
Publication Date
2025-03-04
Estimated Expiration
2042-11-10

AI Technical Summary

Technical Problem

The existing electromagnetic microwave absorbing materials have low absorption performance, narrow absorption bandwidth and high filler content, making it difficult to meet the protection needs of precision electronic equipment.

Method used

The three-dimensional porous composite material MXene/TMS is used to induced the assembly of MXene nanosheets into hydrogels through divalent transition metal ions such as Co2+ as crosslinking agents, and then lyophilized and pyrolyzed to form Ti3C2Tx MXene as the conductive backbone. The in-situ transformed TMS nanoparticles are anchored on the three-dimensional backbone to form a non-uniform heterogeneous interface and defect-induced dipole polarization sites.

Benefits of technology

It improves the loss ability and absorption bandwidth of electromagnetic waves, reduces the filler content of the material, and enhances the dielectric polarization ability of the material. It is suitable for electromagnetic microwave absorption and infrared stealth applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115716648B_ABST
    Figure CN115716648B_ABST
Patent Text Reader

Abstract

The present invention provides a three-dimensional porous composite material and a preparation method and electromagnetic microwave absorption application thereof, which relates to the field of electromagnetic microwave absorption of nanocomposite materials. In the present invention, a divalent transition metal ion TM is first used. 2+ , such as Co 2+ As a crosslinker, Ti3C2T x Adding transition metal ion solution into MXene suspension induces Ti3C2T with negative potential. x MXene nanosheets rapidly gel to form MXene / Co via electrostatic interactions 2+ The hydrogel is further freeze-dried and vulcanized under pyrolysis conditions to form a lightweight MXene / CoS aerogel composite material. The unique three-dimensional porous structure is conducive to meeting the important prerequisite of electromagnetic waves entering the interior of the microwave absorber, and Ti3C2T x MXene as a conductive skeleton is beneficial to improve the charge transport capacity. At the same time, the in-situ converted CoS nanoparticles are anchored in the three-dimensional Ti3C2T x On the MXene skeleton, non-uniform heterogeneous interfaces and defect-induced dipole polarization sites are formed, which further enhance the dielectric polarization ability of the composite material and improve the loss capacity of electromagnetic waves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electromagnetic microwave absorption of nanocomposite materials, and in particular to a three-dimensional porous composite material and a preparation method and electromagnetic microwave absorption application thereof. Background Art

[0002] With the widespread use of electromagnetic functional devices, smart devices bring convenience to people's lives, but also have serious electromagnetic radiation effects on people's physical health. Living under electromagnetic wave radiation for a long time poses a serious threat to people's physical and mental health. In addition, precision electronic instruments will be affected by the interference of electromagnetic waves, which will affect the normal use of the instruments and reduce the service life of the instruments.

[0003] Based on this, it is urgent to explore high-performance electromagnetic microwave absorbing materials to convert unnecessary electromagnetic waves into heat or other forms of energy. At present, electromagnetic microwave absorbing materials are mainly magnetic loss materials. However, due to the high density of magnetic materials, high filler content, dielectric loss capacity and poor impedance matching characteristics, their application in some precision electronic instruments and equipment is limited. The development of lightweight and high-performance electromagnetic microwave absorbing materials can effectively protect human health and precision electronic equipment.

[0004] In addition, in fields such as military, the development of electromagnetic microwave and infrared compatible stealth materials has greater application potential value. Summary of the invention

[0005] 1. Technical issues to be solved

[0006] In view of the deficiencies in the prior art, the present invention provides a three-dimensional porous composite material, a preparation method thereof and an electromagnetic microwave absorption application, which solves the technical problems of low absorption performance, narrow absorption bandwidth and high filler content of current electromagnetic microwave absorption materials.

[0007] (II) Technical solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] A three-dimensional porous composite material, wherein the three-dimensional porous composite material is MXene / TMS, comprising:

[0010] Divalent transition metal ions TM 2+ As a cross-linking agent, it induces MXene nanosheets to assemble into MXene / TM 2+ Hydrogel, aerogel obtained after freeze drying of hydrogel is Ti3C2T x MXene is used as a conductive skeleton, and the in-situ converted TMS nanoparticles are anchored in the three-dimensional porous Ti3C2T xOn the MXene skeleton, non-uniform heterointerfaces and defect-induced dipole polarization sites are formed.

[0011] Preferably, the divalent transition metal ion is Co 2+ , Fe 2+ , Ni 2+ , Cu 2+ or Zn 2+ .

[0012] A method for preparing a three-dimensional porous composite material, comprising:

[0013] Step S1, adding the raw material Ti3AlC2 into a mixed etching solution of hydrochloric acid and lithium fluoride, etching the Al layer in the raw material under water bath conditions, and then ultrasonically peeling it off in an ice bath, centrifuging to obtain a few layers of MXene aqueous solution and refrigerating it for later use;

[0014] Step S2: Add the prepared divalent transition metal ion solution into the MXene solution, and shake the solution until it gels to form MXene / TM 2+ Hydrogel and freeze-dried to obtain MXene / TM 2+ Aerogel, vacuum storage for future use;

[0015] Step S3: preparing the MXene / TM 2+ Aerogel and thiourea were placed in a tubular furnace and pyrolyzed under the protection of nitrogen. When the temperature was cooled to room temperature, three-dimensional porous Ti3C2T x MXene aerogels confine metal sulfide composites MXene / TMS.

[0016] Preferably, the etching solution in step S1 is prepared by adding 1 to 4 g of LiF to 20 to 40 ml of 9 to 12 mol / L HCl solution.

[0017] Preferably, in step S1, 1-2.4 g of the raw material Ti3AlC2 is added to a hydrochloric acid / lithium fluoride mixed etching solution, the reaction temperature is controlled to be 30-45°C, the continuous stirring time is 18-48 hours, centrifugation and water washing are performed until the pH value is 5.5-7, and the ultrasonic time is 50-80 minutes.

[0018] Preferably, the concentration of the few-layer MXene nanosheet suspension obtained in step S1 is 10 to 25 mg / ml.

[0019] Preferably, in step S2, the concentration of the divalent transition metal ions is 0.10 to 0.20 g / mL, the volume of the added transition metal ion solution is 0.5 to 1 mL, and the volume of the MXene nanosheet suspension is 2 to 8 mL.

[0020] Preferably, the freeze-drying conditions in step S2 are -55°C and 24h.

[0021] Preferably, the amount of thiourea in step S3 is 0.5 to 2 g.

[0022] Preferably, in step S3, the pyrolysis vulcanization temperature is 300-500° C., the reaction time is 1-3 h, and the heating rate and cooling rate are both 1-3° C. / min.

[0023] Preferably, in step S1:

[0024] The etched MXene solution was centrifuged and washed with water until the pH value of the upper layer of the solution was 5.5-7, then 50-150 mL of deionized water was added and the solution was placed in an ultrasonic machine for ultrasonic treatment in an ice bath for 50-80 min.

[0025] Preferably, the divalent transition metal ion in step S2 is Co 2+ , Fe 2+ , Ni 2+ , Cu 2+ or Zn 2+ .

[0026] An application of electromagnetic microwave absorption, characterized in that the three-dimensional porous composite material as described above or the three-dimensional porous composite material prepared by the preparation method as described above is applied to electromagnetic microwave absorption.

[0027] (III) Beneficial effects

[0028] The present invention provides a three-dimensional porous composite material and a preparation method and electromagnetic microwave absorption application thereof. Compared with the prior art, it has the following beneficial effects:

[0029] In the present invention, the unique three-dimensional porous structure is conducive to satisfying the important premise that electromagnetic waves enter the interior of the microwave absorber, and Ti3C2T x MXene as a conductive skeleton is beneficial to improve the charge transport capacity. At the same time, the in-situ converted CoS nanoparticles are anchored in the three-dimensional Ti3C2T x On the MXene skeleton, non-uniform heterogeneous interfaces and defect-induced dipole polarization sites are formed, which further enhance the dielectric polarization ability of the composite material and improve the loss capacity of electromagnetic waves. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 Scanning electron microscope images of MXene / CoS (a), MXene / FeS (b), MXene / NiS (c), MXene / CuS (d), and MXene / ZnS (e) provided in an embodiment of the present invention;

[0032] Figure 2 The three-dimensional porous Ti3C2T x TEM image of MXene / CoS, a MXene aerogel-confined metal sulfide composite material;

[0033] Figure 3 The three-dimensional porous Ti3C2T x Schematic diagram of the process for preparing MXene aerogel-confined metal sulfide composites;

[0034] Figure 4 A MXene / CoS (a), MXene / FeS (b), MXene / NiS (c), MXene / CuS (d), MXene / ZnS (e) three-dimensional porous Ti3C2T provided in the embodiments of the present invention x MXene aerogel-confined metal sulfide composite performance diagram;

[0035] Figure 5 A MXene / FeS (a), MXene / NiS (b), MXene / CuS (c), MXene / ZnS (d) three-dimensional porous Ti3C2T provided in the embodiments of the present invention x MXene aerogel-confined metal sulfide composite performance diagram;

[0036] Figure 6 The three-dimensional porous Ti3C2Tx MXene aerogel provided in the embodiment of the present invention defines the minimum reflection loss and effective absorption bandwidth comparison of various metal sulfide composite materials;

[0037] Figure 7 A diagram showing the infrared stealth performance of a three-dimensional porous Ti3C2Tx MXene aerogel-confined metal sulfide composite material provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The embodiments of the present application solve the technical problems of low absorption performance, narrow absorption bandwidth and high filler content of current electromagnetic microwave absorption materials by providing a three-dimensional porous composite material, a preparation method thereof and electromagnetic microwave absorption application.

[0040] The technical solution in the embodiment of the present application is to solve the above technical problems, and the overall idea is as follows:

[0041] In the embodiment of the present invention, the unique three-dimensional porous structure is conducive to satisfying the important prerequisite of electromagnetic waves entering the interior of the microwave absorber, and Ti3C2T x MXene as a conductive skeleton is beneficial to improve the charge transport capacity. At the same time, the in-situ converted CoS nanoparticles are anchored in the three-dimensional Ti3C2T x On the MXene skeleton, non-uniform heterogeneous interfaces and defect-induced dipole polarization sites are formed, which further enhance the dielectric polarization ability of the composite material and improve the loss capacity of electromagnetic waves.

[0042] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0043] First, as Figures 1-2 As shown, the embodiment of the present invention provides a three-dimensional porous Ti3C2T x MXene aerogels define metal sulfide composites, the three-dimensional porous Ti3C2T x MXene aerogels are limited to metal sulfide composites MXene / TMS (MXene / FeS, MXene / NiS, MXene / CuS, MXene / ZnS), including:

[0044] Divalent transition metal ions TM 2+ As a cross-linking agent, it induces MXene nanosheets to assemble into MXene / TM 2+ Hydrogel, aerogel obtained after freeze drying of hydrogel is Ti3C2T x MXene is used as a conductive skeleton, and the in-situ converted TMS nanoparticles are anchored in the three-dimensional porous Ti3C2T x On the MXene skeleton, non-uniform heterointerfaces and defect-induced dipole polarization sites are formed.

[0045] in, Figure 1 Scanning electron microscope images of MXene / CoS (a), MXene / FeS (b), MXene / NiS (c), MXene / CuS (d), and MXene / ZnS (e) provided in an embodiment of the present invention; Figure 2 TEM image of the three-dimensional porous Ti3C2Tx MXene aerogel-confined metal sulfide composite material MXene / CoS provided in an embodiment of the present invention.

[0046] Second, as Figure 3 As shown, the embodiment of the present invention provides a three-dimensional porous Ti3C2T x A method for preparing a MXene aerogel-confined metal sulfide composite material, comprising:

[0047] Step S1, adding the raw material Ti3AlC2 into a mixed etching solution of hydrochloric acid and lithium fluoride, etching the Al layer in the raw material under water bath conditions, and then ultrasonically peeling it off in an ice bath, centrifuging to obtain a few layers of MXene aqueous solution and refrigerating it for later use;

[0048] Step S2: Add the prepared divalent transition metal ion solution into the MXene solution, and shake the solution until it gels to form MXene / TM 2+ Hydrogel and freeze-dried to obtain MXene / TM 2+ Aerogel, vacuum storage for future use;

[0049] Step S3: preparing the MXene / TM 2+ Aerogel and thiourea were placed in a tubular furnace and pyrolyzed under the protection of nitrogen. When the temperature was cooled to room temperature, three-dimensional porous Ti3C2T x MXene aerogels confine metal sulfide composites MXene / TMS.

[0050] In a third aspect, an embodiment of the present invention provides a three-dimensional porous Ti3C2T x The application of MXene aerogel-limited metal sulfide composite materials is to form a three-dimensional porous Ti3C2T x MXene aerogel-confined metal sulfide composite material or a three-dimensional porous Ti3C2T prepared by any of the preparation methods described above x MXene aerogel-confined metal sulfide composites for electromagnetic microwave absorption.

[0051] In the embodiment of the present invention, the divalent transition metal ion TM is first used 2+ , such as Co 2+ As a crosslinker, Ti3C2Tx Adding transition metal ion solution into MXene suspension induces Ti3C2T with negative potential. x MXene nanosheets rapidly gel to form MXene / Co via electrostatic interactions 2+ The hydrogel was further freeze-dried and vulcanized under pyrolysis conditions to form a lightweight MXene / CoS aerogel composite.

[0052] The unique three-dimensional porous structure is conducive to satisfying the important premise that electromagnetic waves enter the interior of the microwave absorber, and Ti3C2T x MXene as a conductive skeleton is beneficial to improve the charge transport capacity. At the same time, the in-situ converted CoS nanoparticles are anchored in the three-dimensional Ti3C2T x On the MXene skeleton, non-uniform heterogeneous interfaces and defect-induced dipole polarization sites are formed, which further enhance the dielectric polarization ability of the composite material and improve the loss capacity of electromagnetic waves.

[0053] In addition, this induced Ti3C2T x The MXene gelation method can be extended to other types of divalent transition metal ions (Fe 2+ , Ni 2+ , Cu 2+ , Zn 2+ ), and further freeze-dried and in-situ vulcanized to obtain the corresponding MXene / TMS (MXene / FeS, MXene / NiS, MXene / CuS, MXene / ZnS) aerogel composites. And the three-dimensional porous aerogel exhibits excellent infrared stealth performance.

[0054] Embodiment 1:

[0055] S1. Add 1.5g Ti3AlC2 raw material to a mixed etching solution of hydrochloric acid and lithium fluoride, control the reaction temperature to 35℃, stir continuously for 24h, wash repeatedly, centrifuge with deionized water several times, until the pH value of the supernatant reaches about 6-7. Etch the Al layer in the raw material under water bath conditions and peel it off by ultrasonic treatment in an ice bath for 1h, then centrifuge at 3500rpm for 1h to obtain a few layers of MXene aqueous solution and refrigerate for later use (~15mg / mL);

[0056] The hydrofluoric acid solution was prepared by adding 1 g of LiF to 20 ml of 9M HCl (15 mL of hydrochloric acid / 5 mL of deionized water) solution.

[0057] S2, add 0.5 mL of the prepared 0.15 g / mL CoCl2 solution to the 6 mL of 15 mg / mL MXene solution prepared in S1, and gently shake the solution until it quickly gels to form MXene / Co 2+ The hydrogel was freeze-dried for 24 h to obtain MXene / Co 2+ Aerogel, and vacuum storage for future use;

[0058] S3, 0.1g MXene / Co prepared in step S2 2+ The aerogel and 0.5 g of thiourea were placed in a tubular furnace and pyrolyzed at 400 °C for 2 h under the protection of N2 gas. The heating and cooling rate was 2 °C / min. When the temperature was cooled to room temperature, a three-dimensional porous Ti3C2T x MXene / CoS aerogel composites.

[0059] like Figure 4 As shown in (a), the three-dimensional porous Ti3C2T x The minimum reflection loss of MXene / CoS aerogel composite material reaches -69.6dB at a thickness of 3.5mm, and the effective absorption bandwidth covers the X-band (8.2-12.4GHz).

[0060] Embodiment 2:

[0061] The embodiment of the present invention provides a three-dimensional porous Ti3C2T x A method for preparing a MXene aerogel-confined metal sulfide composite material, comprising:

[0062] S1. Add 1.5g Ti3AlC2 raw material to a mixed etching solution of hydrochloric acid and lithium fluoride, control the reaction temperature to 35℃, stir continuously for 24h, wash repeatedly, centrifuge with deionized water several times, until the pH value of the supernatant reaches about 6-7. Etch the Al layer in the raw material under water bath conditions and peel it off by ultrasonic treatment in an ice bath for 1h, then centrifuge at 3500rpm for 1h to obtain a few layers of MXene aqueous solution and refrigerate for later use (~15mg / mL);

[0063] The hydrofluoric acid solution was prepared by adding 1 g of LiF to 20 ml of 9M HCl (15 mL of hydrochloric acid / 5 mL of deionized water) solution.

[0064] S2, add 0.5 mL of the prepared 0.15 g / mL CoCl2 solution to the 6 mL of 15 mg / mL MXene solution prepared in S1, and gently shake the solution until it quickly gels to form MXene / Co 2+ The hydrogel was freeze-dried for 24 h to obtain MXene / Co 2+Aerogel, and vacuum storage for future use;

[0065] S3, 0.1g MXene / Co prepared in step S2 2+ The aerogel and 0.5 g thiourea were placed in a tubular furnace and pyrolyzed at 300 °C for 2 h under the protection of N2 gas. The heating and cooling rate was 2 °C / min. When the temperature was cooled to room temperature, a three-dimensional porous Ti3C2T x MXene / CoS aerogels confined metal sulfide composites.

[0066] like Figure 4 As shown in (b), the three-dimensional porous Ti3C2T x The minimum reflection loss of MXene / CoS aerogel composite material reaches -23.46dB at a thickness of 5.0mm, and the effective absorption bandwidth is 1.92GHz.

[0067] Embodiment 3:

[0068] The embodiment of the present invention provides a three-dimensional porous Ti3C2T x A method for preparing a MXene aerogel-confined metal sulfide composite material, comprising:

[0069] S1. Add 1.5g Ti3AlC2 raw material to a mixed etching solution of hydrochloric acid and lithium fluoride, control the reaction temperature to 35℃, stir continuously for 24h, wash repeatedly, centrifuge with deionized water several times, until the pH value of the supernatant reaches about 6-7. Etch the Al layer in the raw material under water bath conditions and peel it off by ultrasonic treatment in an ice bath for 1h, then centrifuge at 3500rpm for 1h to obtain a few layers of MXene aqueous solution and refrigerate for later use (~15mg / mL);

[0070] The hydrofluoric acid solution was prepared by adding 1 g of LiF to 20 ml of 9M HCl (15 mL of hydrochloric acid / 5 mL of deionized water) solution.

[0071] S2, add 0.5 mL of the prepared 0.15 g / mL CoCl2 solution to the 6 mL of 15 mg / mL MXene solution prepared in S1, and gently shake the solution until it quickly gels to form MXene / Co 2+ The hydrogel was freeze-dried for 24 h to obtain MXene / Co 2+ Aerogel, and vacuum storage for future use;

[0072] S3, 0.1g MXene / Co prepared in step S2 2+The aerogel and 0.5 g of thiourea were placed in a tubular furnace and pyrolyzed at 500 °C for 2 h under the protection of N2 gas. The heating and cooling rate was 2 °C / min. When the temperature was cooled to room temperature, a three-dimensional porous Ti3C2T x MXene / CoS aerogels confined metal sulfide composites.

[0073] like Figure 4 As shown in (c), the three-dimensional porous Ti3C2T x The minimum reflection loss of MXene / CoS aerogel composite material reaches -32.2dB at a thickness of 3.5mm, and the effective absorption bandwidth is 3.36GHz.

[0074] Embodiment 4:

[0075] The embodiment of the present invention provides a three-dimensional porous Ti3C2T x A method for preparing a MXene aerogel-confined metal sulfide composite material, comprising:

[0076] S1. Add 1.5g Ti3AlC2 raw material to a mixed etching solution of hydrochloric acid and lithium fluoride, control the reaction temperature to 35℃, stir continuously for 24h, wash repeatedly, centrifuge with deionized water several times, until the pH value of the supernatant reaches about 6-7. Etch the Al layer in the raw material under water bath conditions and peel it off by ultrasonic treatment in an ice bath for 1h, then centrifuge at 3500rpm for 1h to obtain a few layers of MXene aqueous solution and refrigerate for later use (~15mg / mL);

[0077] The hydrofluoric acid solution was prepared by adding 1 g of LiF to 20 ml of 9M HCl (15 mL of hydrochloric acid / 5 mL of deionized water) solution.

[0078] S2, add 0.5 mL of the prepared 0.15 g / mL FeCl2 solution to the 15 mg / mL 6 mL MXene solution prepared in S1, and gently shake the solution until it quickly gels to form MXene / Fe 2+ The hydrogel was freeze-dried for 24 h to obtain MXene / Fe 2+ Aerogel, and vacuum storage for future use;

[0079] S3, 0.1 g MXene / Fe prepared in step S2 2+ The aerogel and 0.5 g of thiourea were placed in a tubular furnace and pyrolyzed at 400 °C for 2 h under the protection of N2 gas. The heating and cooling rate was 2 °C / min. When the temperature was cooled to room temperature, a three-dimensional porous Ti3C2T x MXene / FeS aerogels confined metal sulfide composites.

[0080] like Figure 5 As shown in (a), the three-dimensional porous Ti3C2T x The minimum reflection loss of MXene / FeS aerogel composite material reaches 42.58dB at a thickness of 5.0mm, and the effective absorption bandwidth is 2.87GHz.

[0081] Embodiment 5:

[0082] The embodiment of the present invention provides a three-dimensional porous Ti3C2T x A method for preparing a MXene aerogel-confined metal sulfide composite material, comprising:

[0083] S1. Add 1.5g Ti3AlC2 raw material to a mixed etching solution of hydrochloric acid and lithium fluoride, control the reaction temperature to 35℃, stir continuously for 24h, wash repeatedly, centrifuge with deionized water several times, until the pH value of the supernatant reaches about 6-7. Etch the Al layer in the raw material under water bath conditions and peel it off by ultrasonic treatment in an ice bath for 1h, then centrifuge at 3500rpm for 1h to obtain a few layers of MXene aqueous solution and refrigerate for later use (~15mg / mL);

[0084] The hydrofluoric acid solution was prepared by adding 1 g of LiF to 20 ml of 9M HCl (15 mL of hydrochloric acid / 5 mL of deionized water) solution.

[0085] S2, add 0.5 mL of the prepared 0.15 g / mL NiCl2 solution to the 6 mL of 15 mg / mL MXene solution prepared in S1, and gently shake the solution until it quickly gels to form MXene / Ni 2+ The hydrogel was freeze-dried for 24 h to obtain MXene / Ni 2+ Aerogel, and vacuum storage for future use;

[0086] S3, 0.1g MXene / Ni prepared in step S2 2+ The aerogel and 0.5 g of thiourea were placed in a tubular furnace and pyrolyzed at 400 °C for 2 h under the protection of N2 gas. The heating and cooling rate was 2 °C / min. When the temperature was cooled to room temperature, a three-dimensional porous Ti3C2T x MXene / NiS aerogel confined metal sulfide composites.

[0087] like Figure 5 As shown in (b), the three-dimensional porous Ti3C2T x The minimum reflection loss of MXene / NiS aerogel composite material reaches 68.11dB at a thickness of 2.5mm, and the effective absorption bandwidth is 3.56GHz.

[0088] Embodiment 6:

[0089] The embodiment of the present invention provides a three-dimensional porous Ti3C2T x A method for preparing a MXene aerogel-confined metal sulfide composite material, comprising:

[0090] S1. Add 1.5g Ti3AlC2 raw material to a mixed etching solution of hydrochloric acid and lithium fluoride, control the reaction temperature to 35℃, stir continuously for 24h, wash repeatedly, centrifuge with deionized water several times, until the pH value of the supernatant reaches about 6-7. Etch the Al layer in the raw material under water bath conditions and peel it off by ultrasonic treatment in an ice bath for 1h, then centrifuge at 3500rpm for 1h to obtain a few layers of MXene aqueous solution and refrigerate for later use (~15mg / mL);

[0091] The hydrofluoric acid solution was prepared by adding 1 g of LiF to 20 ml of 9M HCl (15 mL of hydrochloric acid / 5 mL of deionized water) solution.

[0092] S2, add 0.5 mL of the prepared 0.15 g / mL CuCl2 solution to the 6 mL of 15 mg / mL MXene solution prepared in S1, and gently shake the solution until it quickly gels to form MXene / Cu 2+ The hydrogel was freeze-dried for 24 h to obtain MXene / Cu 2+ Aerogel, and vacuum storage for future use;

[0093] S3, 0.1g MXene / Cu prepared in step S2 2+ The aerogel and 0.5 g of thiourea were placed in a tubular furnace and pyrolyzed at 400 °C for 2 h under the protection of N2 gas. The heating and cooling rate was 2 °C / min. When the temperature was cooled to room temperature, a three-dimensional porous Ti3C2T x MXene / CuS aerogels confined metal sulfide composites.

[0094] like Figure 5 As shown in (c), the three-dimensional porous Ti3C2T x The minimum reflection loss of the MXene / CuS aerogel composite material reaches -18.6dB at a thickness of 1.9mm, and the effective absorption bandwidth is 1.84GHz.

[0095] Embodiment 7:

[0096] The embodiment of the present invention provides a three-dimensional porous Ti3C2T x A method for preparing a MXene aerogel-confined metal sulfide composite material, comprising:

[0097] S1. Add 1.5g Ti3AlC2 raw material to a mixed etching solution of hydrochloric acid and lithium fluoride, control the reaction temperature to 35℃, stir continuously for 24h, wash repeatedly, centrifuge with deionized water several times, until the pH value of the supernatant reaches about 6-7. Etch the Al layer in the raw material under water bath conditions and peel it off by ultrasonic treatment in an ice bath for 1h, then centrifuge at 3500rpm for 1h to obtain a few layers of MXene aqueous solution and refrigerate for later use (~15mg / mL);

[0098] The hydrofluoric acid solution was prepared by adding 1 g of LiF to 20 ml of 9M HCl (15 mL of hydrochloric acid / 5 mL of deionized water) solution.

[0099] S2, add 0.5 mL of the prepared 0.15 g / mL ZnCl2 solution to the 6 mL of 15 mg / mL MXene solution prepared in S1, and gently shake the solution until it quickly gels to form MXene / Zn 2+ The hydrogel was freeze-dried for 24 h to obtain MXene / Zn 2+ Aerogel, and vacuum storage for future use;

[0100] S3, 0.1 g MXene / Zn prepared in step S2 2+ The aerogel and 0.5 g of thiourea were placed in a tubular furnace and pyrolyzed at 400 °C for 2 h under the protection of N2 gas. The heating and cooling rate was 2 °C / min. When the temperature was cooled to room temperature, a three-dimensional porous Ti3C2T x MXene / ZnS aerogel confined metal sulfide composites.

[0101] like Figure 5 As shown in (d), the three-dimensional porous Ti3C2T x The minimum reflection loss of the MXene / ZnS aerogel composite material reaches -26.9dB at a thickness of 1.9mm, and the effective absorption bandwidth is 2.76GHz.

[0102] In the embodiment of the present invention, the electromagnetic parameters are obtained by using a vector network analyzer. Paraffin wax is mixed with the prepared three-dimensional porous Ti3C2T x MXene aerogel-confined metal sulfide composite material (15wt%) was uniformly mixed, and after vacuum heating and melting, the mixed material was pressed into a coaxial ring sample with an outer diameter of 7.0mm, an inner diameter of 3.04mm, and a thickness of 2.5mm using a mold. The electromagnetic parameters of the coaxial ring sample were tested using a vector network analyzer (Ceyear 3656D). The minimum reflection loss (RL) at different thicknesses was fitted according to the transmission line theory formula.

[0103]

[0104]

[0105] Where Z in is the effective input impedance, Z0 is the free space impedance, ε r =ε′-jε″ and μ r =μ′-jμ″ respectively represent the dielectric constant and complex magnetic permeability, f is the frequency, d is the corresponding thickness, and c is the speed of light in vacuum.

[0106] from Figure 4 Three-dimensional porous Ti3C2T x The change in the minimum reflection loss curve at the corresponding thickness of the MXene aerogel-limited metal sulfide composite material (Example 1 above) shows that the composite material exhibits excellent microwave absorption performance and a wide effective absorption bandwidth and exhibits electromagnetic microwave absorption performance related to the thermal vulcanization temperature. Figure 4 (a) It can be seen that the three-dimensional porous MXene / CoS-S2 (above Example 1) aerogel has a minimum reflection loss of -69.6dB at a thickness of 3.5mm, and the effective absorption bandwidth covers the X-band (8.2-12.4GHz). When the temperature during the vulcanization process is lowered or increased, the aerogel composite material shows a decrease in electromagnetic microwave absorption performance (above Examples 2 and 3), which shows that the electromagnetic microwave absorption performance can be optimized to an ideal state by controlling the preparation temperature.

[0107] also, Figure 5 MXene / FeS, MXene / NiS, MXene / CuS, and MXene / ZnS aerogel composites are formed by anchoring different metal sulfides on the three-dimensional MXene aerogel skeleton. Figure 5 (a) Three-dimensional porous Ti3C2T x The MXene / FeS aerogel composite material has a minimum reflection loss of 42.58 dB at a thickness of 5.0 mm and an effective absorption bandwidth of 2.87 GHz (Example 4). Figure 5 (b) Three-dimensional porous Ti3C2T x The MXene / NiS aerogel composite material has a minimum reflection loss of 68.11 dB at a thickness of 2.5 mm and an effective absorption bandwidth of 3.56 GHz (Example 5). Figure 5 (c) Three-dimensional porous Ti3C2T x The minimum reflection loss of the MXene / CuS aerogel composite material reaches -18.6 dB at a thickness of 1.9 mm, and the effective absorption bandwidth is 1.84 GHz (Example 6). Figure 5 (d) Three-dimensional porous Ti3C2T xThe minimum reflection loss of the MXene / ZnS aerogel composite material reaches -26.9 dB at a thickness of 1.9 mm, and the effective absorption bandwidth is 2.76 GHz (Example 7).

[0108] Figure 6 The minimum reflection loss and effective absorption bandwidth of different metal sulfides anchored in 3D MXene aerogels are compared; and Figure 7 As shown, the three-dimensional porous aerogel exhibits excellent infrared stealth performance.

[0109] The three-dimensional porous Ti3C2T x The excellent electromagnetic microwave absorption performance of MXene aerogel-limited metal sulfide composite material MXene / TMS is mainly attributed to the following aspects:

[0110] First, the unique three-dimensional porous structure is conducive to satisfying the important premise that electromagnetic waves enter the interior of the microwave absorber, and Ti3C2T x MXene as a conductive skeleton is beneficial to improve the charge transport capacity. At the same time, the in-situ converted transition metal sulfide nanoparticles are anchored in the three-dimensional Ti3C2T x On the MXene skeleton, non-uniform heterogeneous interfaces and defect-induced dipole polarization sites are formed, which further enhance the dielectric polarization ability of the composite material and improve the loss capacity of electromagnetic waves.

[0111] Secondly, the embodiment of the present invention adopts self-assembly and heteroepitaxial method to prepare electromagnetic microwave absorption multi-level heterostructure composite material, which shows low reflection loss and wide effective absorption bandwidth. In addition, the three-dimensional porous aerogel shows excellent infrared stealth performance.

[0112] Finally, the embodiment of the present invention uses MXene nanosheets with good conductivity as the three-dimensional skeleton, and synthesizes three-dimensional porous Ti3C2T2 by electrostatic interaction and in-situ sulfurization. x MXene aerogel-confined metal sulfide composite materials. The raw materials, equipment and process used in this method are simple, low-cost, simple and safe to operate, low-cost, clean and environmentally friendly, and are conducive to large-scale production.

[0113] In summary, compared with the prior art, the present invention has the following beneficial effects:

[0114] 1. In the embodiment of the present invention, a divalent transition metal ion TM is first used 2+ , such as Co 2+ As a crosslinker, Ti3C2T x Adding transition metal ion solution into MXene suspension induces Ti3C2T with negative potential. xMXene nanosheets rapidly gel to form MXene / Co via electrostatic interactions 2+ The hydrogel was further freeze-dried and vulcanized under pyrolysis conditions to form a lightweight MXene / CoS aerogel composite.

[0115] 2. The unique three-dimensional porous structure is conducive to satisfying the important premise of electromagnetic waves entering the interior of the microwave absorber, and Ti3C2T x MXene as a conductive skeleton is beneficial to improve the charge transport capacity. At the same time, the in-situ converted CoS nanoparticles are anchored in the three-dimensional Ti3C2T x On the MXene skeleton, non-uniform heterogeneous interfaces and defect-induced dipole polarization sites are formed, which further enhance the dielectric polarization ability of the composite material and improve the loss capacity of electromagnetic waves.

[0116] 3. In addition, this induced Ti3C2T x The MXene gelation method can be extended to other types of divalent transition metal ions (Fe 2+ , Ni 2+ , Cu 2+ , Zn 2+ ), and further freeze-dried and in-situ vulcanized to obtain the corresponding MXene / TMS (MXene / FeS, MXene / NiS, MXene / CuS, MXene / ZnS) aerogel composites. And the three-dimensional porous aerogel exhibits excellent infrared stealth performance.

[0117] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0118] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A three-dimensional porous composite material, characterized in that: Applied to electromagnetic microwave absorption, the three-dimensional porous composite material is MXene / TMS, including: Divalent transition metal ions TM 2+ As a cross-linking agent, it induces MXene nanosheets to assemble into MXene / TM 2+ Hydrogel, aerogel obtained after freeze drying of hydrogel is Ti3C2T x MXene is used as a conductive skeleton, and the in-situ converted TMS nanoparticles are anchored in the three-dimensional porous Ti3C2T x On the MXene skeleton, non-uniform heterointerfaces and defect-induced dipole polarization sites are formed.

2. The three-dimensional porous composite material according to claim 1, characterized in that: The divalent transition metal ion is Co 2 + , Fe 2+ , Ni 2+ , Cu 2+ or Zn 2+ .

3. A method for preparing the three-dimensional porous composite material as claimed in claim 1, characterized in that: include: Step S1, adding the raw material Ti3AlC2 into a mixed etching solution of hydrochloric acid and lithium fluoride, etching the Al layer in the raw material under water bath conditions, and then ultrasonically peeling it off in an ice bath, centrifuging to obtain a few layers of MXene aqueous solution and refrigerating it for later use; Step S2: Add the prepared divalent transition metal ion solution into the MXene solution, and shake the solution until it gels to form MXene / TM 2+ Hydrogel and freeze-dried to obtain MXene / TM 2+ Aerogel, vacuum storage for future use; Step S3: preparing the MXene / TM 2+ Aerogel and thiourea were placed in a tubular furnace and pyrolyzed under the protection of nitrogen. When the temperature was cooled to room temperature, three-dimensional porous Ti3C2T x MXene aerogels confine metal sulfide composites MXene / TMS.

4. The preparation method according to claim 3, characterized in that: The etching solution in step S1 is prepared by adding 1 to 4 g of LiF to 20 to 40 ml of 9 to 12 mol / L HCl solution; And / or in step S1, 1-2.4 g of the raw material Ti3AlC2 is added to a hydrochloric acid / lithium fluoride mixed etching solution, the reaction temperature is controlled to be 30-45°C, the continuous stirring time is 18-48 hours; centrifugation and water washing are performed until the pH value is 5.5-7; and the ultrasonic time is 50-80 minutes; And / or the concentration of the few-layer MXene nanosheet suspension obtained in step S1 is 10 to 25 mg / ml.

5. The preparation method according to claim 3, characterized in that: In step S2, the concentration of the divalent transition metal ion is 0.10-0.20 g / mL, the volume of the added transition metal ion solution is 0.5-1 mL, and the volume of the MXene nanosheet suspension is 2-8 mL; And / or the freeze-drying conditions in step S2 are -55°C and 24h.

6. The preparation method according to claim 3, characterized in that: The amount of thiourea in step S3 is 0.5 to 2 g; And / or in step S3, the pyrolysis and vulcanization temperature is 300-500° C., the reaction time is 1-3 hours, and the heating rate and cooling rate are both 1-3° C. / min.

7. The preparation method according to any one of claims 3 to 6, characterized in that: In step S1: The etched MXene solution was centrifuged and washed with water until the pH value of the upper layer of the solution was 5.5-7, then 50-150 mL of deionized water was added and the solution was placed in an ultrasonic machine for ultrasonic treatment in an ice bath for 50-80 min.

8. The preparation method according to any one of claims 3 to 6, characterized in that: In step S2, the divalent transition metal ion is selected from Co 2+ , Fe 2+ , Ni 2+ , Cu 2+ or Zn 2+ .

9. An application of electromagnetic microwave absorption, characterized in that: The three-dimensional porous composite material as claimed in any one of claims 1 to 2 or the three-dimensional porous composite material prepared by the preparation method as claimed in any one of claims 3 to 8 is applied to electromagnetic microwave absorption.

Citation Information

Patent Citations

  • Three-dimensional compound structure based on three-dimensional MXene and general synthesis method thereof

    CN108516528A

  • Preparation and application of CoS / Ti3C2 MXene composite material

    CN114849748A